Edukasi Kesehatan Ispa Pada Balita Di Posyandu RT.06 RW.02 Puskesmas Jalan Gedang Kota Bengkulu - Okti Afriyani; Apriani, Welian; Andani, Meri; Putri , Widia Eka; Lestari , Widhia; Anggraini, Nesi; Aprianti, Delta (Utami Publisher, 2025)
ISPA (Acute Respiratory Tract Infection) is an acute infectious disease that attacks one or more respiratory organs that can last for 2 weeks. Based on data from the DKI Jakarta Health Office, approximately 1.9 million cases of ISPA were recorded from early January to October 2025. South Jakarta alone handled 453,725 ISPA cases until October 2025. Meanwhile, the Bengkulu City Health Office showed an astonishing number, with 5,142 ISPA cases in toddlers (children under five years old) and 24,849 cases in children over five years old during the period from January to September 2025. Acute Respiratory Tract Infection (ISPA) is caused by bacteria and viruses. ISPA is often suffered by children and is also a major killer. This outreach activity aims to help reduce the transmission of ISPA and increase knowledge about ISPA in children at Posyandu RT.06 RW.02, Jalan Gedang Village, Gading Cempaka District, Bengkulu City. ARI is consistently ranked second most frequently occurring disease based on the number of visits to the Jalan Gedang Community Health Center in Bengkulu City. The method used in outreach is education about ARI. This is expected to increase public awareness of ISPA, thereby reducing the rate of ISPA transmission.